Dual Plasma Sampling Method to Determine the Hepatic and Renal Clearance of the 2 Diastereoisomers of Gd-EOB-DTPA. Issue 3 (March 2020) - Yuan, Xiaodong; Wang, Su; Shi, Wenwei; Cai, Yu; Chen, Yingxin; Chen, Ming; Peng, Yanghong; Ao, Guokun
Abstract : Objectives: The aim of this study was to develop a method to determine hepatic and renal clearance of the 2 diastereoisomers (Gd-A, Gd-B) of Gd-EOB-DTPA separately. Materials and Methods: Between July 2017 and February 2018, 41 patients with hepatic disease were prospectively included. For each patient, 1 mL of iopromide (to determine glomerular filtration rate [GFR]) was coadministered with Gd-EOB-DTPA (Gd-A and Gd-B; 65:35 wt/wt). The plasma clearances of Gd-A (PCL-GdA) and Gd-B (PCL-GdB) as well as the iopromide (GFR) were generated by using dual plasma sampling method. Meanwhile, the patient's urine was collected for measurement of renal clearance of Gd-A (RCL-GdA) and Gd-B (RCL-GdB) to confirm its agreement with GFR. Hepatic clearances of Gd-A (HCL-GdA) and Gd-B (HCL-GdB) were calculated by subtracting the GFR from PCL-GdA and PCL-GdB, respectively, and were correlated with indocyanine green (ICG) 15 minutes retention rate (ICG R15). Pharmacokinetic parameters were compared between the two isomers and between Child–Pugh classifications using student's t test. Results: Within the group of 41 patients evaluated, both RCL-GdA and RCL-GdB demonstrated a good correlation and agreement to GFR (statistics shown in the main body). HCL-GdA demonstrated a strong negative correlation ( r = −0.86, P < 0.001) with ICG R15 and was much higher than HCL-GdB (116.18 ± 75.48 vs 19.74 ± 14.24 mL/min, P < 0.001). HCL-GdB demonstrated a weak correlation ( r = −0.26, P = 0.102) with ICG R15. HCL-GdA of noncirrhosis and Child-Pugh class A (151.74 ± 68.28 mL/min, n = 26) was higher than that of Child-Pugh class B (54.54 ± 39.13 mL/min, n = 15; P = 0.001). Conclusions: A practical method was established for the determination of hepatic and renal clearance of the 2 isomers of Gd-EOB-DTPA. The 2 isomers have equal renal clearance and different hepatic clearance. The HCL-GdA may serve as a novel marker to reflect liver function reserve. Abstract : Supplemental digital content is available in the text.